La conscience des animaux - Le Neindre, P.; Dunier, Muriel; Larrère, Raphaël; Prunet, Patrick (éditions Quae, 2018)
Can animals experience emotions? Do they have a life story? The INRA addressed these questions by performing a collective scientific assessment of animal consciousness. This multidisciplinary evaluation, in which a vast body of behavioral, cognitive and neurobiological studies is analyzed, tends to show the existence of conscious thought processes in animals.